2017
DOI: 10.1002/2016jc012238
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide during the onset of the Atlantic cold tongue

Abstract: The tropical Atlantic exerts a major influence in climate variability through strong air‐sea interactions. Within this region, the eastern side of the equatorial band is characterized by strong seasonality, whereby the most prominent feature is the annual development of the Atlantic cold tongue (ACT). This band of low sea surface temperatures (∼22–23°C) is typically associated with upwelling‐driven enhancement of surface nutrient concentrations and primary production. Based on a detailed investigation of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
(158 reference statements)
4
15
1
Order By: Relevance
“…Atmospheric N 2 O data were linearly interpolated over the time of the cruises and then used for the computation of the equilibrium concentrations, saturations, and sea-air fluxes of N 2 O. Sea-air flux densities of N 2 O (F N 2 O ) were computed as described in Arévalo-Martínez et al (2017) with instantaneous wind speeds taken from the ship's weather system (standardized to 10 m height; Garrat, 1977). N 2 O saturations (N 2 O sat ) were obtained from the concentration (C) ratio between seawater (sw) and atmospheric equilibrium (atm) values (N 2 O sat = C sw /C atm ·100).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric N 2 O data were linearly interpolated over the time of the cruises and then used for the computation of the equilibrium concentrations, saturations, and sea-air fluxes of N 2 O. Sea-air flux densities of N 2 O (F N 2 O ) were computed as described in Arévalo-Martínez et al (2017) with instantaneous wind speeds taken from the ship's weather system (standardized to 10 m height; Garrat, 1977). N 2 O saturations (N 2 O sat ) were obtained from the concentration (C) ratio between seawater (sw) and atmospheric equilibrium (atm) values (N 2 O sat = C sw /C atm ·100).…”
Section: Data Processingmentioning
confidence: 99%
“…N 2 O saturations (N 2 O sat ) were obtained from the concentration (C) ratio between seawater (sw) and atmospheric equilibrium (atm) values (N 2 O sat = C sw /C atm ·100). Sea-air flux densities of N 2 O (F N 2 O ) were computed as described in Arévalo-Martínez et al (2017) with instantaneous wind speeds taken from the ship's weather system (standardized to 10 m height; Garrat, 1977).…”
Section: Data Processingmentioning
confidence: 99%
“…Additionally, Arévalo-Martínez et al (2017) showed, based on an inverse relationship between N 2 O and sea surface temperature, that N 2 O-enriched waters are transported to the surface during the upwelling season in the equatorial Atlantic. In areas like the equatorial Atlantic where nitrification is the major pathway of N 2 O formation (Arévalo-Martínez et al, 2017;Walter et al, 2006;Yoshida et al, 1989), NH 2 OH can be, therefore, interpreted as an indicator for active nitrification. Furthermore, a significant amount of oceanic N 2 O is thought to originate from archaeal rather than from bacterial nitrification (Löscher et al, 2012;Santoro et al, 2011).…”
Section: Nh 2 Oh and N 2 O Discrepancymentioning
confidence: 99%
“…However, this is the first time showing that there is a significant correlation between NH 2 OH and N 2 O in the open ocean. In areas like the equatorial Atlantic where nitrification is the major pathway of N 2 O formation (Arévalo-Martínez et al, 2017;Walter et al, 2006;Yoshida et al, 1989), NH 2 OH can be, therefore, interpreted as an indicator for active nitrification.…”
Section: Nh 2 Oh and N 2 O Discrepancymentioning
confidence: 99%
See 1 more Smart Citation